Association of Herpes Simplex Virus Testing with Hospital Length of Stay for Infants ≤60 Days of Age Undergoing Evaluation for Meningitis. Issue 8 (1st August 2019) - Aronson, Paul L; Cruz, Andrea T; Freedman, Stephen B; Balamuth, Fran; Grether‐Jones, Kendra L; Lyons, Todd W; Fleming, Alesia H; Louie, Jeffrey; Mistry, Rakesh D; Garro, Aris C; Shah, Samir S; Nigrovic, Lise E; et al.
Abstract : Although neonatal herpes simplex virus (HSV) causes significant morbidity, utilization of the cerebrospinal fluid (CSF) HSV polymerase chain reaction (PCR) test remains variable. Our objective was to examine the association of CSF HSV PCR testing with length of stay (LOS) in a 20‐center retrospective cohort of hospitalized infants aged ≤60 days undergoing evaluation for meningitis after adjustment for patient‐level factors and clustering by center. Of 20, 496 eligible infants, 7, 399 (36.1%) had a CSF HSV PCR test performed, and 46 (0.6% of those tested) had a positive test. Infants who had a CSF HSV PCR test performed had a 23% longer hospital LOS (incident rate ratio 1.23; 95% CI: 1.14‐1.33). Targeted CSF HSV PCR testing may mitigate the impact on LOS for low‐risk infants.